Occupational stress and coping resources in physiotherapists: a survey of physiotherapists in three general hospitals - Santos, Manuel C. (2015)
Objectives - To identify occupational stressors and coping resources in a group of physiotherapists, and to analyse interactions between subjective levels of stress, efficacy in stress resolution and coping resources used by these professionals. Design - A sample of 55 physiotherapists working in three general hospitals in Portugal completed the Coping Resources Inventory for Stress, the Occupational Stressors Inventory and two subjective scales for stress and stress resolution. Main results - Most physiotherapists perceived that they were moderately stressed (19/55, 35%) or stressed (20/55, 36%) due to work, and reported that their efficacy in stress resolution was moderate (25/54, 46%) or efficient (23/54, 42%). Issues related to lack of professional autonomy, lack of organisation in the hierarchical command chain, lack of professional and social recognition, disorganisation in task distribution and interpersonal conflicts with superiors were identified as the main sources of stress. The most frequently used coping resources were social support, stress monitoring, physical health and structuring. Perceived efficacy in stress resolution was inversely related to perceived level of occupational stress (r = −0.61, P < 0.01). Significant correlations were found between several coping resources and the perceived level of stress and efficacy in stress resolution. Associations between problem solving, cognitive restructuring and stress monitoring and both low levels of perceived stress and high levels of perceived efficacy were particularly strong. Implications for practice - The importance of identifying stressors and coping resources related to physiotherapists’ occupational stress, and the need for the development of specific training programmes to cope with stress are supported.